Analisis Sentimen Komentar TikTok terhadap Kebijakan Larangan Wisuda Sekolah oleh Gubernur Jawa Barat Menggunakan Algoritma Naive Bayes - Setiawan, Kiki; Alafia, Evi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research focuses on analyzing public sentiment regarding the policy banning school graduation ceremonies in West Java, which aims to adapt the tradition to socio-economic conditions. This research is expected to provide insights for the formulation of more inclusive and equitable education policies, as well as offer alternative, more friendly graduation practices. The research object includes public opinions and comments on the social media app TikTok regarding this policy. The method used is sentiment analysis with the Naive Bayes algorithm, with data collected over two months following the policy's announcement. The results show that the majority of respondents support the ban, driven by reasons of reducing the burden on parents' costs and minimizing social jealousy. The conclusion can be drawn that this policy has received a positive response from the public. These findings can serve as a reference for policymakers in developing a more equitable education system. It is recommended that the government continue to involve the public in the policy-making process and seek alternative methods for celebrating graduations that are more economical and equitable.